preparation of some diamidophosphoric acid derivitives (Baghdad Science Journal, 2005)
Reacts compound C6H5PO2Cl2 with Secretary secondary R2NH at room temperature by Mulet 2:1 and using chloroform as a solvent in dry conditions to form composite 2HCl and the interaction of compound solution of sodium hydroxide and potassium by Mulet 3:1 salt was prepared